Annual world Bank Conference on development Economics 2001/2002 : [proceedings] - Stern, Nicholas; World Bank Annual Conference on Development Economics Washington, D.C 2002; Pleskovic, Boris (Washington,D.C World Bank, 2002)
​This report for 2001-2002 focuses on two main themes, based on papers presented, and discussions that followed: 1) globalization and inequality, drawing on historical trends, through the human capital nexus, and the role of foreigntrade and investment, to the geographic and international inequalities of globalization, and how the impact of technological change affected the developing world; and, 2) health and development, focused on the role of nongovernmental organizations in the provision of health care, with a special look at the patent policy proposal for global diseases. Health, income, and economic developments are emphasized, so as to highlight the world inequality, and the growing concerns on the rising longevity.
Introduction / Boris Pleskovic, Nichola Stern and F. Desmond McCarthy-- Globalization and Inequality: Globalization and Inequality: historical trends / Kevin H. O’rourke -- Fear of globalization: the human capital nexus / Daniel cohen -- Growth and inequality: the role of foreign trade and investment / Richard N. Cooper -- Geography and international inequities: the impact of new technologies / Anthony J. Venables -- Health and development: The role of nongovernmental organizations in providing health care / Morten Rostrup -- A patent policy proposal for global diseases / Jean O. Lanjouw -- Health, income, and development / Anne Case -- World inequality and the rise in longevity / Tomas Philipson and Rodrigo R. Soares
Includes bibligraphies
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPMENT POLICY; SOCIAL INEQUALITY; HEALTH; Globalization; ECONOMIC RESEARCH; DEVELOPING COUNTRIES; CONFERENCES